Methodology of training leg movements in middle school age basketballers - Jiang Liang; Maksimenko I.G. (Theory and Practice of Physical Culture, 2025)
Objective of the study. To substantiate the method of training leg movements in basketball players of middle school age. Methods and structure of the study. The research materials include theoretical sources of Russian and Chinese authors, which relate to the issue under study. In addition, also important material is the pedagogical experiment conducted by the author of the work and the analysis of the results of this experiment. Research methods: 1. Analysis of theoretical sources. 2. Methodological analysis. 3. Pedagogical experiment. Results of the study and their discussion. The main problems that prevent athletes from revealing their own potential in basketball are insufficient share of observation, difficulties with quick reaction time and problems with controlling the balance of their own body. The paper provides recommendations to solve these problems and contradictions. An experiment was conducted in the paper, the results of which allowed to clearly see the effectiveness of the proposed recommendations. If at the beginning of the experiment the indicators of the participants of the experimental group were lower than those of the participants of the control group, then by the time of the experiment completion and retesting the ratio changed in the opposite direction.